Pengaruh Literasi Ekonomi dan Internal Locus of Control Terhadap Minat Entrepreneurship pada Siswa Kelas XII Sekolah Menengah Kejuruan (SMK) Swasta 2 Mulia Medan - Maretta Ginting; Ronnie Togar Mulia Sirait; Hilda Syaf’aini Harefa (Jurnal EMT KITA, 2023)
The purpose of this study is to determine, in part and simultaneously, the effects of economic literacy and internal control on the entrepreneurial interest satisfaction of students in Class XII of Private Vocational High School (SMK) 2 Mulia Medan. The study population consisted of 37 class XII students from Private Vocational High School 2 Muria Medan. The sample for this survey consisted of 37 respondents using a saturated sampling technique. The analytical methods used are instrumental testing, classical hypothesis testing, hypothesis testing, certainty testing, and multiple regression analysis. The results show that (1) based on subtests (t-tests), financial literacy has a positive and significant effect on entrepreneurial interest among students in Class XII of Private Vocational High School (SMK) 2 Mulia Medan, (2) a subtest-based (t-test) Internal Locus of Control, and (3) a simultaneous test of economic literacy (F-Test) and, based on the Internal Locus of Control, between private class XII students and interested in entrepreneurship at the same time. Vocational High School (SMK) 2 Mulia Medan.